Β‐Cyclodextrin–Glycerol Dimers: Synthesis and NMR Conformational Analysis. Issue 13 (13th March 2013) - Legros, Vanessa; Vanhaverbeke, Cécile; Souard, Florence; Len, Christophe; Désiré, Jérôme
Abstract: The synthesis of new β‐cyclodextrin dimers linked through their primary faces by different glycerol‐like moieties by click chemistry is described. The unusual behaviour of these cyclodextrin–glycerol dimers in aqueous solution has been studied by NMR spectroscopy. We show that, depending on the length of the linking arm between the two cyclodextrins, the dimers could adopt very different conformations in water: symmetrical or pseudo[1]rotaxane‐like structures through oneD ‐glucopyranose unit tumbling in one β‐cyclodextrin. Abstract : Six β‐cyclodextrin (CD) dimers linked through their primary faces by different types of glycerol arms were synthesized by click chemistry. Of them, one CD dimer showed symmetrical and pseudo[1]rotaxane‐like conformations in D2 O. Evidence for tumbling of one of the glucopyranose units with the chain, changing the depth of inclusion of the linker in the CD cavity, was obtained by NMR spectroscopy.